Das Wagnis des Scheiterns Religionspädagogische und -didaktische Untersuchungen zu einem Erfahrungsfeld der Gegenwart - Novakovits, David (Kohlhammer Verlag, 2023)
In sociological, philosophical and psychoanalytical perspectives, an interdisciplinary discourse is designed that names both the depths and potentials of the experiential field of failure. In a didactic transformation of religion, three narrative learning arrangements are developed: the story of the Tower of Babel, the prodigal son and a story from early Christianity: the historia lausiaca, the nameless fool. These are designed to enable students to question the narrative of the optimised human being and to interpret the vulnerability and precariousness of the human as more than a mere loss of ultimate sovereignty and autonomy.